Pacific - agricultural trade policy debates and developments: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Rising food prices are a major cause for concern in Pacific ACP countries, given these countries’ high food import dependency (ranging from 36% in Kiribati to 84% in Palau). Despite considerable constraints on land, poor transport infrastructure, and the adverse effects of climate change, Pacific ACP governments are focusing on expanding domestic food production both for local markets and for export. For the latter, emphasis is being placed on niche marketing and value addition activities, although policy debates are aiming to find a balance between small-scale production (widespread in the region) and the promotion of investment in larger-scale commercial production. This Executive Brief focuses on 2012-13 developments in the Pacific ACP agricultural sector, analyzing the trends in intra-regional trade and the relations with third countries, mainly the EU, Australia and New Zealand.